HOW DO INDONESIAN IN-SERVICE EFL TEACHERS DEFINE WRITING PRACTICE AND WRITING INSTRUCTION: A MICROECOLOGICAL PERSPECTIVE - Nuriska Noviantoro; Muslim Ahmad Bukhori; Yanty Wirza (University of Kuningan, 2025)
Despite global shifts towards process-oriented L2 writing instruction, a theory-practice gap persists in Indonesia, where pedagogy often remains product-focused. This study investigates how Indonesian in-service English teachers formulate their beliefs about writing practices and instruction through an ecological lens. A qualitative case study design was employed, involving 20 voluntary high school teachers from Yogyakarta during a professional development program. Data were collected through narrative frames, written narratives, and semi-structured interviews, and analyzed via qualitative content analysis to identify emergent themes. Findings revealed a fragile instructional microsystem, primarily constrained by teachers’ own identities as writers. A significant lack of writing self-efficacy led many to adopt protective, control-oriented pedagogies, such as sentence-level drills and corrective feedback, despite espousing beliefs in process-oriented approaches. This growth mindset paradox highlighted how internal insecurities and external pressures (e.g., administrative burdens, student readiness) undermined the implementation of constructive beliefs. The study concludes that an effective reform must address teachers’ personal writing competencies, suggesting that professional development should focus on building their identity and confidence as writers to foster more authentic, process-focused writing classrooms.